A Subsistence Linked Economy : The Case of the Solomon Islands. (IMF Working Papers; Working Paper ;, 1989)
How are money demand, income, and the price level affected when a significant portion of the economically active population reverts to and withdraws from subsistence economic activity? This paper tries to find a quantitative answer to the question by highlighting the specific link between the monetized and the subsistence economy that exists in the Solomon Islands: the producer price of copra, the main cash crop. The paper includes this variable explicitly in the money demand function of an aggregated macroeconomic simultaneous equation model and finds a significant impact throughout the economy.